KEMAMPUAN MENULIS NARASI SUGESTIF SISWA KELAS X SMANEGERI 1 TAMBUSAI KABUPATEN ROKAN HULU - Fitri Yana; Mangatur Sinaga; Abdul Jalil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This research’s title is Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency. The research’s problems are (1) Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in delivering implicit message, (2) Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in building imagination, (3) Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using figurative language, (4) Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using connotation language, (5) Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using figure of a language. This research aims is to know Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in delivering implicit message, Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in building imagination, Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using figurative language, Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using connotation language, Writing Suggestive Narration Skill of Ten Grade Students at SMA Negeri 1 Tambusai Rokan Hulu Regency in using figure of a language. The method is descriptive. The data collection technique in this research is used test technical. The population is 184 students and the sample of this research is 46 students by random. To analyze this research used average formulation by using criteria in reaching competence. The analysis the research’s data is done to (1) 46 essays Suggestive Narration implicit message, (2) 40 essays Suggestive Narration in imagination’s aspect, (3) 8 essays Suggestive Narration figurative language, (4) 4 essays Suggestive Narration connotation aspect, and (5) 9 essays Suggestive Narration  figure of a language. This research was identification that (1) Writing Suggestive Narration skill in delivering implicit message is high category, (2) Writing Suggestive Narration skill in building imaginations is high category, (3) Writing Suggestive Narration skill in using figurative language is low category, (4) Writing Suggestive Narration Skill in using connotation language is low category, (5) Writing Suggestive Narration Skill in using figure of a language is low category.Keywords         : Skill, Writing,  Suggestive Narration